Treatment options for relapse after autograft in multiple myeloma - report from an EBMT educational meeting - Garderet, Laurent; Schönland, Stefan (Leukemia and lymphoma, 2017)
Major improvements have been made in the treatment of myeloma. However, all patients, perhaps with some exceptions, eventually relapse, even after autologous stem cell transplantation (ASCT). In that setting, the combinations of new drugs, namely the IMiDs and the proteasome inhibitors along with steroids, give encouraging results in relapsed patients. The median progression-free survival (PFS) is 20 months with lenalidomide plus dexamethasone plus ixazomib and 26 months with lenalidomide plus dexamethasone plus carfilzomib. Monoclonal antibodies have emerged as an additional new treatment option. The antibody anti-SLAMF7, elotuzumab, in combination with lenalidomide plus dexamethasone gives a median PFS of 20 months. The antibody daratumumab, targeting CD38, alone has an outstanding activity in previously heavily treated patients. Its use in combination is ongoing. Transplantation remains a major treatment option. For patients who relapse at least 18 months from the initial ASCT, a second ASCT can be performed with an expected time to progression of 19 months from the time of transplantation. For patients relapsing earlier and/or with high-risk characteristics and who are still chemosensitive, with a suitable donor, an allogeneic transplantation can be considered. The optimal treatment combination and sequence remain to be determined.
Published online: 21 Sep 2016
Gesehen am 21.06.2018